DAMPAK BULLYING VERBAL TERHADAP PERILAKU SISWA DI SMA NEGERI 3 PAYAKUMBUH - Eka Afriani; Afrinaldi Afrinaldi (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
This study aims to explore the impact of bullying on student behavior at SMA Negeri 3 Payakumbuh. Verbal bullying is an aggressive act in the form of speech that is done intentionally and repeatedly with the aim of dominating, showing strength, hurting, terrorizing, or just for fun. This research is a qualitative research in the form of descriptive. Data collection techniques used are observation and interviews. The results of the study showed the impact of verbal bullying that occurred at SMA Negeri 3 Payakumbuh on student behavior, namely decreased self-confidence, became gloomy, decreased socialization levels, and decreased academic grades. Verbal bullying occurs during empty class hours, recess hours, sports hours, and school hours. The reason for the perpetrators of verbal bullying is the habit in the place where they come from as normal, they think they are the strongest, they want to be respected, and there is no resistance from the victim.